AN AUTOMATED MATERIAL HANDLING PLC-BASED CONTROL SYSTEM VIA SEQUENTIAL FUNCTION CHART WITH IoT IMPLEMENTATION - CHETTIAR KAVANDAN, PUVENTIRAN (2018)
The usage of PLC is essential in almost all the manufacturing industry sectors. This is due to the effectiveness of PLC in terms of programming structure and also the flexibility in changing the outputs based on the standards set. In order to enhance the the flow of control of PLC , concept of Internet of Things ( IoT ) is approached to alter the control process of automated material handling in manufacturing sector and to cater the industry 4.0 concept as well. In industrial sector , this concept is being implemented step by step as the technology demand helps in boosting the productivity rate. Therefore , a study have been conducted by the author on automated material handling PLC-based control system via Sequential Function Chart aided by IoT to analyse the importance and benefits of using manufacturing systems which is helped by the contribution of PLC and also IoT. The overall process required a bluetooth connection to cater as a communication medium between the PLC and the mobile phone , which was used to implement the idea of IoT in this project. Commands was sent from the mobile phone to the PLC , in this project context the mobile phone was used to ON/OFF switch for the PLC via bluetooth. Once, the command had been sent the actuators movement can be observed as programmed in PLC. A mobile app was developed in the laptop via an app inventor website and was shared to the mobile phone. The programming languages approached in programming the PLC ( Programmable Logic Controller ) are Ladder Diagram and also Sequential Function Chart which are two of the five programming languages according to the standards of IEC 61131-3.